A STUDY ON LANGUAGE LEARNING STRATEGIES OF XI GRADE STUDENTS IN ADVANCED AND REGULAR CLASS OF NATURAL SCIENCE PROGRAM AT SMAN 1 DAMPIT - ANTIKA, MAULIDA MADYA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Inventory for Language Learning (SILL) questionnaire. English is considered as an important language and it makes the Indonesian government decrees English as one of the school subjects to develop the ability of Indonesian people in English. The application of government’s decrees is by making National Standard School (SSN) which has advanced and regular class program. This program classifies the students based on their ability and takes English as important subject in learning process. In order to be successful in English learning, the students need to know language learning strategies for increasing their academic achievement and increasing ability of English. This study is conducted to investigate the application of language learning strategies of the XI grade students in advanced and regular class of Natural Science Program at SMAN 1 Dampit.The research design of this study is quantitative approach since it examines phenomenon in detail. The subjects in this study are 140 second grade students comprising 27 students from advanced class and 113 students from regular class of Natural Science Program at SMAN 1 Dampit. The data was obtained using Strategy Inventory for Language Learning (SILL) questionnaire completed by advanced and regular class students.The results show that the application of language learning strategies in advanced class and regular class are different. Advanced class students most frequently use cognitive strategies and regular class tends to use compensation strategy as the most frequently used strategy. The overall mean score of advanced class in language learning strategies usage is higher than the regular class. The difference of the overall mean score between advanced class and regular class is influenced by different teaching system used for both classes and from the students themselves such as motivation or environments of the students.In conclusion, giving different teaching system can influence theapplication of language learning strategies. By knowing the language learning strategies used by advanced and regular students, the teachers can give appropriate language learning strategies training to advanced and regular students to increase their English ability. Keywords: language learning strategy, advanced and regular class, Strategy